"THE FREQUENCY OF CORYNEBACTERIUM UREALYTICUM IN PATIENTS WITH RENAL STONES" - A. Bordji (Acta Medica Iranica, 2004)
Urinary stones are prevalent and Corynebacterium urealyticum, a urease-positive bacteria, is a frequent urinary tract pathogen. However, the association of this organism with urinary stones is not sufficiently studied in Iran. This study was carried out to determine the prevalence of C. urealyticum in patients with urinary stones referred to the urology sections of Tehran University of Medical Sciences. This study was performed using case-control method. A total of 150 urine samples from patients with urinary stones and the same number from the control group without urinary stones or infection were collected. The two sets of samples were cultured and biochemically identified. The pH of urine samples also measured with pH paper. C. urealyticum was detected in 11.34% of cases which was significantly higher than that in control group (P < 0.01). The frequency of alkaline urine was four times more in the patients than those in control group which was statistically significant (P< 0.01). According to the results, C. urealyticum, which is known to cause alkaline urine, might enhance formation of stones. Further studies using cohort or experimental methods are recommended.